Upgrading homesteads to flood shelters in char Kochkhali, Gaibandha - Adham, Md. Rubayet IBN (BRAC University, 2011)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Master in Disaster Management, 2010.